PELATIHAN SANTRI PP. SALAFIYAH SYAFI’IYAH SITUBONDO DALAM PEMANFAATAN LIMBAH UDANG VANNAME SEBAGAI MSG ALAMI - Ika Junia Ningsih; Ismi Jasila; Lovi Sandra; Abdul Muqsith (LP2M Universitas Ibrahimy, 2023)
This research aimed to determine the application of natural flavoring powder processed from shrimp waste. Natural MSG (Monosodium glutamate) which plays a role in shrimp waste due to the presence of glutamic acid in it. Flavoring is a component of cooking that can provide flavors to food. As an alternative to using flavoring shrimp waste can be used as a basic ingredient of flavoring high protein and safe for health. The implementation method is carried out through 3 steps, (1) preparation and briefing, (2) implementation of program and (3) evaluation of the implementation of program. This activity was welcomed by the enthusiasm of the residents and was attended by around 50 trainess. The results of the program show that the process of making shrimp broth powder has been very well carried out in accordance with the directions for processing procedures and also ran smoothly followed by enthusiastic trainees following. Assessment of the characteristics of shrimp broth powder showed that the appearance of shrimp broth powder was very uniform and intact, had a light brown color, had a smooth texture, and had a delicious taste.